VD_FINDINFO Décision / 2012 / 885 vom 31. Juli 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, INFRACTIONS CONTRE L'HONNEUR | 173 CP, 174 CP, 319 al. 1 CPP (CH), 393 al. 1 let. a CPP (CH)